Prepreg containing wide melting limit polyamide particles and high toughness and high shear strength composite materials

By using the combination of wide-melt limited polyamide particles with fiber and resin matrix, the problem of weak interface binding force of polyamide particles is solved, and the interlayer shear strength and impact toughness of the composite material are improved, and it is suitable for high-performance aerospace materials.

CN115895189BActive Publication Date: 2024-12-13AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211405577.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-10
Publication Date
2024-12-13
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

The interface bonding force between existing polyamide particles and matrix resins is weak, resulting in increased interlayer toughness of composite materials but decreased interlayer shear strength, especially when high impact toughness demands, resulting in poor actual results.

Method used

Wide melt limit polyamide particles are adopted, with a melting point between 160 and 225℃ and a melting limit between 15 and 60℃. They are combined with fibers and uncured resin matrix to form a strong interfacial bonding force, enhancing the interlayer shear strength and impact toughness of the composite material. .

Benefits of technology

The high interlayer shear strength and impact toughness of the composite material are achieved, and the compression strength after impact reaches 348MPa, and can be used in combination with other particles to further improve the compression strength after impact, which is suitable for aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003936554590000061
    Figure BDA0003936554590000061
  • Figure BDA0003936554590000071
    Figure BDA0003936554590000071
Patent Text Reader

Abstract

The present invention discloses a prepreg containing wide melting limit polyamide particles and a high-toughness and high-shear strength composite material, belonging to the technical field of composite materials. The prepreg comprises reinforcing fibers and an uncured resin matrix; the uncured resin matrix comprises a resin component, a curing agent, a soluble thermoplastic toughening agent and thermoplastic toughening particles, wherein the resin component comprises at least one epoxy resin, and the thermoplastic toughening particles comprise wide melting limit polyamide particles. The wide melting limit polyamide particles have crystalline regions and non-crystalline regions, which can maintain the thickness and regularity of the toughening layer and form an interpenetrating network with the matrix resin, so that the post-impact compression strength and interlaminar shear strength of the composite material can be significantly improved, meeting the requirements of the aerospace field for high impact toughness of carbon fiber composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a prepreg containing wide melting limit polyamide particles and a high-toughness and high-layer interlaminar shear strength composite material made of the prepreg, belonging to the technical field of composite materials. Background Art

[0002] Polymer-based composite materials have the advantages of high specific modulus, high specific strength, strong designability, excellent fatigue resistance, etc. Compared with metal materials, they have obvious structural weight reduction benefits and have become one of the main structural materials used in the contemporary aerospace field. For example, composite parts such as wings, fuselages, bulkheads and control surfaces are manufactured by molding and curing pre-impregnated composite materials (prepregs). The use of prepregs to manufacture composite parts can accurately control the amount and position of resin impregnated into the fiber network, ensuring the distribution of resin and fiber in the composite material, so that the composite material has sufficient mechanical properties.

[0003] The impact resistance of composite materials is a bottleneck that limits their application in aerospace and other fields. Thermosetting resin systems (such as epoxy resins, bismaleimide resins, etc.) usually have the disadvantages of low elongation at break and poor damage tolerance after curing. The corresponding composite materials show insufficient interlayer toughness. When subjected to low-speed impact, large-scale delamination is likely to occur between the layers, which seriously affects the load-bearing capacity and service life of the composite materials. Therefore, it is necessary to toughen the composite materials to improve their resistance to impact damage and delamination.

[0004] The interlaminar toughening method of thermoplastic resin particles can effectively improve the impact impedance and damage tolerance of thermosetting resin-based composite materials. The interlaminar particle toughening technology utilizes the advantages of thermosetting resin matrix and thermoplastic resin particles, and concentrates the thermosetting resin matrix with good process performance and high modulus in the fiber layer to achieve fiber infiltration, while the thermoplastic resin particles with excellent fracture toughness are mainly enriched in the interlaminar of the composite material, giving full play to its advantages of high fracture toughness, preventing the laminate from delamination damage and inhibiting the excessive expansion of cracks in the interlaminar resin matrix.

[0005] Interlayer particle toughening is currently the most commonly used, most mature and most extensive composite material toughening method. At present, the M21 and M91 systems of Hexel Corporation of the United States, the 3900 and 3960 systems of Toray Industries, Japan, and the X850 system of Cytec Technology Co., Ltd. of the United States all adopt interlayer particle toughening methods, which significantly improves the damage tolerance of the composite material system. The most critical thing about interlayer particle toughening is to select suitable interlayer toughening particles (thermoplastic resin particles). As early as 2008, in order to improve the damage tolerance of composite materials, Hexel Corporation simultaneously adopted toughening particles with a melting point higher than the curing temperature and toughening particles with a melting point lower than or equal to the curing temperature (CN101679606B). Further, in 2011, Hexel Corporation adopted a blend of insoluble elastic toughening particles and insoluble rigid toughening particles to improve composite material damage tolerance and interlayer toughness (CN102869507B). The toughening particles in these patents all involve different types of polyamides, indicating that polyamide is a preferred toughening particle. Similarly, other multiple patents disclosed by Hexel also involve the use of polyamide as toughening particles (CN104704029B, CN106062051B, CN110337461B). Toray Industries, Ltd. of Japan also reported the toughening effect of different polyamides and prepared different types of polyamide particles (CN104955883B). Cytec Technology Co., Ltd. of the United States uses a combination of insoluble toughening particles and swellable toughening particles in a patent (CN103249776A) to improve the interlaminar toughness of composite materials, which also involves a variety of polyamide particles.

[0006] It can be seen that polyamide is a preferred thermoplastic interlaminar toughening particle. However, there are many types of polyamides, with significant differences in performance, and the toughening effect on composite materials is also different. The above-mentioned patents also show that the melting point, glass transition temperature, crystallinity, particle size, surface morphology, relative molecular weight, end group reactivity of the molecular chain, and mechanical properties such as tension and compression of polyamide will affect its toughening effect on composite materials. Studies have shown that when the melting point of polyamide particles is close to the curing temperature of the matrix resin, a bridging effect can be better formed, thereby greatly improving the impact impedance and damage tolerance of the composite material (Effect of the characteristics of nylon microparticles on Mode-I interlaminar fracture toughness of carbon-fibre / epoxy composites).

[0007] However, even when polyamide particles are selected according to many existing research results, the problem of increasing the interlayer toughness of the composite material while decreasing the interlayer shear strength often occurs, especially in order to obtain high impact toughness, a high content of polyamide particles is often required. This is because the melting point of some polyamide particles is higher than the curing temperature, or the induced crystallization under the high pressure of curing causes the actual melting point of the polyamide to be higher than the curing temperature; the high melting point of polyamide causes it to be unable to form an interpenetrating network structure with the matrix resin during the curing stage of the composite material, and thus cannot form a strong interface bonding force. Therefore, it is necessary to select polyamide particles that can form a strong interface bonding force with the matrix resin, and develop prepregs with high damage tolerance, interlayer fracture toughness and high interlayer shear strength to meet the continuous demand for high-performance prepregs in the aerospace field. Summary of the invention

[0008] The purpose of the present invention is to solve the problem of weak interface bonding between conventional polyamide particles and matrix resins, and to develop a prepreg containing wide melting point polyamide particles and a composite material made of the prepreg with high toughness and high inter-layer shear strength by using a wide melting point polyamide particle. The invention includes the following aspects:

[0009] The first aspect of the present invention provides a prepreg containing wide melting limit polyamide particles, comprising reinforcing fibers and an uncured resin matrix; the uncured resin matrix comprises a resin component, a curing agent, a soluble thermoplastic toughening agent and thermoplastic toughening particles, wherein the resin component comprises at least one epoxy resin, the thermoplastic toughening particles comprise wide melting limit polyamide particles, the wide melting limit polyamide particles have a melting point of 160 to 225°C, preferably 175 to 195°C; the melting limit is 15 to 60°C, preferably 25 to 45°C.

[0010] Preferably, the reinforcing fiber is selected from a combination of one or more of carbon fiber, glass fiber, aramid fiber, and polyimide fiber; more preferably, carbon fiber.

[0011] Preferably, among the reinforcing fibers and the uncured resin matrix, the mass proportion of the uncured resin matrix is ​​25% to 40%, but not limited thereto.

[0012] Preferably, the resin component comprises one or more of a difunctional epoxy resin, a trifunctional epoxy resin and a tetrafunctional epoxy resin, which is a saturated, unsaturated, cycloaliphatic, alicyclic or heterocyclic epoxy resin; the difunctional epoxy resin is selected from a combination of one or more of diglycidyl ether of bisphenol F, diglycidyl ether of bisphenol A, diglycidyl dihydroxynaphthalene, glycidyl ether of phenolic adduct, glycidyl ether of aliphatic diol, diglycidyl ether, diethylene glycol diglycidyl ether, and ... diglycidyl ether of phenolic adduct, diglycidyl ether of aliphatic diol, diglycidyl ether, diglycidyl ether of diethylene glycol, and the difunctional epoxy resin is selected from a combination of one or more of diglycidyl ether of bisphenol F, diglycidyl ether of bisphenol A, diglycidyl dihydroxynaphthalene, diglycidyl ether of phenolic adduct, diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol A, diglycidyl dihydroxynaphthalene, diglycidyl ether of phenolic adduct, diglycidyl ether of bisphenol F, diglycidyl ether of bisphenol A, diglycidyl dihydroxynaphthalene, di The amount of the epoxy resin added is 10wt% to 40wt% of the uncured resin matrix, preferably 15wt% to 35wt%, and more preferably 20wt% to 25wt%; the trifunctional epoxy resin is trifunctional meta-glycidylamine, and the amount of the trifunctional epoxy resin added is 15wt% to 35wt% of the uncured resin matrix, preferably 20wt% to 30wt%; the tetrafunctional epoxy resin is tetrafunctional para-glycidylamine, 5wt% to 15wt%.

[0013] Preferably, the curing agent is one or more of anhydride, aromatic amine, polyol, cyanoguanidine, aromatic, aliphatic amine, acid anhydride, Lewis acid, substituted urea, imidazole and hydrazine, and the amount of the curing agent is 10wt% to 35wt% of the uncured resin matrix, preferably 15wt% to 25wt%.

[0014] Preferably, the soluble thermoplastic toughening agent is selected from one or more combinations of polyethersulfone, polysulfone, polyetherimide, polyimide, polyaryletherketone, polyaryletherketonenitrile, and block copolymer; preferably polyaryletherketone; the amount of the toughening agent is 3wt% to 25wt% of the uncured resin matrix, preferably 10wt% to 20wt%.

[0015] Preferably, the thermoplastic toughened particles further include copolymers of one or more of vinyl polymers, polyesters, polyamides, polyarylethers, polyarylether sulfides, polyethersulfones, polysulfones, polyetherketones, polyetheretherketones, polyurethanes, polycarbonates, polyamideimides, polyimides, polyetherimides, polyacetals, and polysiloxanes; preferably polyamides or polyimides.

[0016] Preferably, the total amount of the thermoplastic toughening particles added is 5wt% to 30wt% of the resin matrix, preferably 5wt% to 15wt%; wherein the amount of the wide melting limit polyamide particles added is 2wt% to 20wt% of the resin matrix, preferably 5wt% to 15wt%.

[0017] The second aspect of the present invention provides a high-toughness and high-shear strength composite material containing wide melting limit polyamide particles, which is prepared by curing a prepreg containing wide melting limit polyamide particles provided in the first aspect of the present invention.

[0018] Advantageous effects of the present invention compared with the prior art

[0019] (1) Since the polyamide particles used in the present invention are wide melting point polyamide particles, more wide melting point polyamide molecular chains can move during the temperature rise and curing stage of the matrix resin, and can form an interpenetrating network structure with the matrix resin to form a stronger interface bond. Therefore, the composite material prepared using wide melting point polyamide particles has high interlaminar shear strength.

[0020] (2) Since wide melting point polyamide particles have crystalline and non-crystalline regions, during the curing of the prepreg, the crystalline region can maintain the thickness and regularity of the toughening layer, and the non-crystalline region can form an interpenetrating network structure with the matrix resin to enhance the interface bonding force; therefore, even if wide melting point polyamide particles are used alone, the effect of using narrow melting point polyamide particles in combination with other particles can be achieved, and the prepared composite material has high impact toughness, and the post-impact compressive strength can reach 348MPa.

[0021] (3) Due to the unique properties of wide melting point polyamide particles, wide melting point polyamide particles can be used to prepare composite materials with both high impact toughness and high interlaminar shear strength. Wide melting point polyamide particles can be used in combination with other particles to further improve the post-impact compressive strength of the composite material, which is greater than 315MPa and up to 374MPa. The high interlaminar shear strength is greater than 110MPa, and can be used in aerospace, rail transportation, weapons and equipment and other fields. DETAILED DESCRIPTION

[0022] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0023] The present invention proposes a prepreg containing wide melting limit polyamide particles, comprising reinforcing fibers and an uncured resin matrix. The reinforcing fibers can be any conventional fibers in the prepreg industry. The uncured resin matrix comprises a resin component, a curing agent, a soluble thermoplastic toughening agent and thermoplastic toughening particles. Among them, the resin component comprises at least one epoxy resin; the thermoplastic toughening particle component comprises wide melting limit polyamide particles, and the melting point of the wide melting limit polyamide particles is 160-225°C, preferably 175-195°C; the melting limit is 15-60°C, preferably 25-45°C. Preferably, the wide melting limit polyamide particles are preferably Arkema's Rislan PA11, Yantai Wanhua's polyamide 12 (commercial brand 1101D), and Hanshuo New Materials' copolymer of polyamide 6 and polyamide 12 (commercial brand 9001).

[0024] According to some embodiments, the reinforcing fiber is selected from a combination of one or more of carbon fiber, glass fiber, aramid fiber, and polyimide fiber; more preferably, carbon fiber.

[0025] According to some embodiments, in the reinforcing fibers and the uncured resin matrix, the mass proportion of the uncured resin is 25% to 40%, but not limited thereto.

[0026] According to some embodiments, the resin component may be a saturated, unsaturated, cycloaliphatic, alicyclic or heterocyclic epoxy resin, and may be one or more of a difunctional epoxy resin, a trifunctional epoxy resin and a tetrafunctional epoxy resin.

[0027] According to some embodiments, the difunctional epoxy resin is exemplified by: diglycidyl ether of bisphenol F, diglycidyl ether of bisphenol A (optionally brominated), diglycidyl dihydroxynaphthalene, glycidyl ether of phenolic adducts, glycidyl ether of aliphatic diols, diglycidyl ether, diethylene glycol diglycidyl ether, or any combination thereof. Most preferably, diglycidyl ether of bisphenol F (Shanghai Huayi Resin Factory 370) is added. The amount of the difunctional epoxy resin added is 10wt% to 40wt% of the uncured resin matrix, preferably 15wt% to 35wt%, and more preferably 20wt% to 25wt%.

[0028] According to some embodiments, the trifunctional epoxy resin is understood to have three epoxy groups directly or indirectly located at the para or meta position on the benzene ring of the main chain of the compound, and trifunctional meta-glycidylamine is selected; the tetrafunctional epoxy resin is understood to have four epoxy groups directly or indirectly located at the para or meta position on the benzene ring of the main chain of the compound, and tetrafunctional para-glycidylamine is selected. A preferred exemplary trifunctional epoxy resin is triglycidyl meta-aminophenol (AFG-90M of Shanghai Huayi Resin Factory). A preferred exemplary tetrafunctional epoxy resin is tetraglycidyl para-aminophenol (1721 of Hanshuo High-tech Materials Co., Ltd.). The addition amount of the trifunctional epoxy resin is 15wt% to 35wt% of the uncured resin matrix, preferably 20wt% to 30wt%. The addition amount of the tetrafunctional epoxy resin is 5wt% to 15wt% of the uncured resin matrix.

[0029] According to some embodiments, the curing agent includes one or more of anhydride, aromatic amine, polyol, cyanoguanidine, aromatic, aliphatic amine, anhydride, Lewis acid, substituted urea, imidazole and hydrazine. Exemplary preferred curing agents include 4,4'-diaminodiphenyl sulfone (4,4'-DDS) and 3,3'-diaminodiphenyl sulfone (3,3'-DDS). The amount of curing agent is 10wt% to 35wt% of the uncured resin matrix, preferably 15wt% to 25wt%.

[0030] According to some embodiments, the soluble thermoplastic toughening agent is usually added to the resin matrix as particles and dissolved in the resin mixture by heating before adding the curing agent, including: polyethersulfone, polysulfone, polyetherimide, polyimide, polyaryletherketone, polyaryletherketonenitrile, block copolymer; preferably polyaryletherketone. The amount of toughening agent is 3wt% to 25wt% of the uncured resin matrix; preferably 10wt% to 20wt%.

[0031] According to some embodiments, the thermoplastic toughening particles can be used alone or mixed with other types of thermoplastic particles. The material of other types of thermoplastic particles is not particularly limited, and can be vinyl polymers, polyesters, polyamides, polyarylethers, polyarylether sulfides, polyethersulfones, polysulfones, polyetherketones, polyetheretherketones, polyurethanes, polycarbonates, polyamide-imides, polyimides, polyetherimides, polyacetals, polysiloxanes and copolymers thereof, etc.; preferably polyamides and polyimides. The total amount of thermoplastic toughening particles added is 5wt% to 30wt% of the uncured resin matrix, preferably 5wt% to 15wt%; wherein the wide melting limit polyamide particles are added in an amount of 2wt% to 20wt% of the resin matrix, preferably 5wt% to 15wt%.

[0032] According to some embodiments, the uncured resin matrix is ​​processed according to a standard prepreg resin matrix, and various epoxy resins are mixed at room temperature to form a resin mixture; a thermoplastic toughening agent is added to the resin mixture, and then heated to about 120° C. and maintained for about 1-2 hours to dissolve the soluble thermoplastic toughening agent; the mixture is then cooled to about 80° C., and the remaining ingredients (thermoplastic particle component, curing agent and other additives (if any)) are mixed into the resin and stirred evenly to form a resin matrix.

[0033] The invention provides a high-toughness and high-shear strength composite material containing wide melting limit polyamide particles, which is prepared by curing a prepreg containing wide melting limit polyamide particles provided by the invention.

[0034] Uncured matrix resin is applied to fiber reinforced material according to any known prepreg manufacturing technology. Fiber reinforced material can be impregnated with matrix resin in whole or in part. Prepreg is usually covered on two faces with a protective film and rolled up for storage and transportation at the following temperature, and the temperature is usually kept far below room temperature to avoid premature curing. The fibrous reinforcement material of prepreg can be selected from mixed or mixed fiber systems, including synthetic fibers or natural fibers, or their combination. This fibrous reinforcement material can preferably be selected from any suitable material, such as glass fiber, carbon fiber or aramid fiber. This fibrous reinforcement material is preferably carbon fiber, can be woven, non-curled, nonwoven, unidirectional or multiaxial fabric structure form.

[0035] The following are several specific embodiments of the present invention, and the raw materials used in each embodiment are commercially available products:

[0036] Embodiments 1 to 4

[0037] Preferred exemplary resin matrix formulations according to the present invention are listed in Table 1. The uncured resin matrix resin preparation steps are as follows: various epoxy resins are mixed at room temperature to form a resin mixture; a thermoplastic toughening agent is added to the resin mixture, and then heated to about 130° C. for about 1-2 hours to dissolve the soluble thermoplastic toughening agent; then the mixture is cooled to about 80° C., the remaining ingredients are mixed into the resin, and stirred to form a resin matrix.

[0038] The steps of preparing the prepreg are as follows: impregnating a unidirectional carbon fiber layer with the resin formulation of Table 1 to form a prepreg consisting of reinforcing fibers and an uncured resin matrix. Among them, the unidirectional carbon fiber used is Guangwei Extension CCFT800H carbon fiber, the resin content is controlled at 34wt%, and the fiber surface density is 194 grams per square meter. The post-impact compressive strength and interlaminar shear strength are carried out according to the corresponding ASTM standards.

[0039] Comparative Example 1

[0040] The resin matrix and the cured prepreg were prepared in the same manner as in Example 1. The difference was that polyamide PA6 particles (1002D) were used instead of wide melting point polyamide PA12 particles (9001). The specific composition and content are shown in Table 1.

[0041] Comparative Example 2

[0042] The resin matrix and the cured prepreg were prepared in the same manner as in Example 2. The difference was that polyamide PA6 particles (1013B) were used instead of polyamide PA11 particles (Rilsan PA11). The specific components and contents are shown in Table 1.

[0043] Comparative Example 3

[0044] The resin matrix and the cured prepreg were prepared in the same manner as in Example 3. The difference was that polyamide PA12 particles (3202D) were used instead of wide melting point polyamide PA12 particles (1101D). The specific composition and content are shown in Table 1.

[0045] Comparative Example 4

[0046] The resin matrix and the cured prepreg were prepared in the same manner as in Example 4. The difference was that polyamide PA6 particles (1013B) were used instead of wide melting point polyamide PA12 particles (9001). The specific composition and content are shown in Table 1.

[0047] Table 1 Different resin matrix formulations

[0048]

[0049]

[0050] Note: (1) Melting point and melting limit were obtained by differential scanning calorimetry (DSC) with a heating rate of 5°C / min.

[0051] (2) The curing process of different prepregs is 180°C for 2 hours, and the heating and cooling rates are 1-3°C / min.

[0052] As can be seen from Table 1, the interlaminar shear strength of the composite material after curing of the prepreg prepared with wide melting limit polyamide particles is relatively high, all higher than 110MPa, which is better than narrow melting limit polyamide particles, especially better than narrow melting limit polyamide particles with a melting point far higher than the curing temperature (about 180°C). This is because the wide melting limit polyamide particles have more polyamide molecular chains that can move during the heating and curing stage of the matrix resin, and are more likely to form an interpenetrating network structure with the matrix resin and thus form a stronger interface layer. However, narrow melting limit polyamide, especially high melting point narrow melting limit polyamide, has fewer active molecular chains and can only form a weak interface layer with the matrix resin.

[0053] It can also be seen from Table 1 that the composite material formed after curing the prepreg prepared with wide melting limit polyamide particles has high impact toughness, and the post-impact compressive strength is higher than 315MPa. In particular, the post-impact compressive strength of the composite material after curing the prepreg prepared with 9001 particles with a melting point of 194°C and a melting limit of 36°C can reach 348MPa, which is higher than the narrow melting limit polyamide particles alone in the comparative example, and also higher than the narrow melting limit polyamide particles combined with other particles in the comparative example. This shows that the use of wide melting limit polyamide particles alone can also achieve the effect of using narrow melting limit polyamide particles in combination with other particles. This is because the wide melting limit polyamide particles have crystalline regions and non-crystalline regions. During the curing of the prepreg, the crystalline region can maintain the thickness and regularity of the toughening layer, and the non-crystalline region can form an interpenetrating network structure with the matrix resin to enhance the interface bonding force.

[0054] It can be further seen from Table 1 that when the wide melting limit polyamide particles are used in combination with other particles, the post-impact compressive strength of the composite material will be further improved, up to 374MPa, which is also better than the combination of narrow melting limit polyamide particles and other particles. In summary, it can be seen that the prepreg prepared with wide melting limit polyamide particles can be used to prepare a composite material with both high impact toughness and high inter-layer shear strength after curing.

[0055] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A prepreg containing wide melting limit polyamide particles, characterized in that: The invention comprises reinforcing fibers and an uncured resin matrix; the uncured resin matrix comprises a resin component, a curing agent, a soluble thermoplastic toughening agent and thermoplastic toughening particles, wherein the resin component comprises at least one epoxy resin, the thermoplastic toughening particles comprise wide melting limit polyamide particles, the melting point of the wide melting limit polyamide particles is 160-225° C., and the melting limit is 31-60° C.

2. The prepreg according to claim 1, wherein the reinforcing fiber is selected from a combination of one or more of carbon fiber, glass fiber, aramid fiber and polyimide fiber.

3. The prepreg according to claim 1, wherein the mass proportion of the uncured resin matrix in the reinforcing fibers and the uncured resin matrix is ​​25% to 40%.

4. The prepreg according to claim 1, wherein the resin component comprises one or more of a difunctional epoxy resin, a trifunctional epoxy resin and a tetrafunctional epoxy resin, and is a saturated or unsaturated alicyclic or heterocyclic epoxy resin.

5. The prepreg as claimed in claim 4, wherein the difunctional epoxy resin is selected from the combination of one or more of the diglycidyl ether of bisphenol F, the diglycidyl ether of bisphenol A, diglycidyl dihydroxynaphthalene, the glycidyl ether of phenolic adducts, diglycidyl ether, and diethylene glycol diglycidyl ether, and its addition amount is 10wt%~40wt% of the uncured resin matrix; the trifunctional epoxy resin is trifunctional meta-glycidyl amine, and its addition amount is 15wt%~35wt% of the uncured resin matrix; the tetrafunctional epoxy resin is tetrafunctional para-glycidyl amine, 5wt%~15wt%.

6. The prepreg according to claim 1, wherein the curing agent is a combination of one or more of anhydride, aromatic amine, polyol, cyanoguanidine, aliphatic amine, substituted urea, imidazole and hydrazine, and the added amount is 10wt% to 35wt% of the uncured resin matrix.

7. The prepreg according to claim 1, wherein the soluble thermoplastic toughening agent is selected from a combination of one or more of polyethersulfone, polysulfone, polyetherimide, polyimide, polyaryletherketone, and polyaryletherketonenitrile, and the added amount is 3wt% to 25wt% of the uncured resin matrix.

8. The prepreg according to claim 1, wherein the thermoplastic toughening particles further comprise a copolymer of one or more of vinyl polymers, polyesters, polyarylethers, polyarylether sulfides, polyethersulfones, polysulfones, polyetherketones, polyetheretherketones, polyurethanes, polycarbonates, polyamideimides, polyimides, polyetherimides, polyacetals, and polysiloxanes; and the total amount of the thermoplastic toughening particles added is 5wt% to 30wt% of the resin matrix.

9. The prepreg according to claim 1, wherein the wide melting limit polyamide particles are added in an amount of 2 wt% to 20 wt% of the resin matrix.

10. A high-toughness and high-shear strength composite material containing wide melting limit polyamide particles, characterized in that: The prepreg according to any one of claims 1 to 9 is prepared by curing.